Pengaruh Manajemen Risiko terhadap Loyalitas Pelanggan Gojek - Setiawan, Farhan; Rachmawati, Eva (Jurnal Ekonomi Manajemen Perbankan, 2025)
Risk management is a crucial process to ensure the achievement of organizational goals and enhance customer trust. In digital business platforms such as Gojek, effective risk management can contribute to increased customer loyalty. This study aims to analyze the influence of risk management on customer loyalty of Gojek users in Bandung, West Java. The research employs a qualitative method with in-depth interviews involving 10 customers who have used Gojek services for at least one year. The findings indicate that Gojek’s risk management has a positive impact on customer loyalty. The company’s efforts include improving safety and security, preventing fraud through an advanced anti-fraud system, and providing fast and transparent complaint handling. These strategies help create a sense of security and build customer trust, ultimately strengthening their loyalty to Gojek’s services.